2008
DOI: 10.1002/bies.20774
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolus of the maternal gamete is essential for life

Abstract: The mammalian oocyte is a round cell arrested at prophase I of meiosis. It is characterized by the presence of a large nucleus, called the germinal vesicle, in the middle of which is the nucleolus. Before it can be fertilized, the oocyte must resume meiosis, enter metaphase II and be ovulated. The nucleolus is dissolved during this process. However, the nucleoli of the male and female pronuclei in the zygote are both of maternal origin. A recent paper1 demonstrates that the maternal nucleolus, together with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…We have also taken into account the chromatin configuration as already described in GV oocytes (Bouniol-Baly et al, 1999;Zuccotti et al, 2002) where the chromatin may be dispersed in the nucleus (NSN) or condensed around the nucleolus (SN). The SN oocytes are considered as more ready to resume meiosis and more able to be fertilized and to have a good embryo development (for review see Lefèvre, 2008).…”
Section: Immunolocalization Of the Three Caspases During The Differenmentioning
confidence: 99%
“…We have also taken into account the chromatin configuration as already described in GV oocytes (Bouniol-Baly et al, 1999;Zuccotti et al, 2002) where the chromatin may be dispersed in the nucleus (NSN) or condensed around the nucleolus (SN). The SN oocytes are considered as more ready to resume meiosis and more able to be fertilized and to have a good embryo development (for review see Lefèvre, 2008).…”
Section: Immunolocalization Of the Three Caspases During The Differenmentioning
confidence: 99%
“…The presence of a nucleolus is not necessary for the spermatozoon, because, after fecundation, the nucleoli of the male and female pronuclei in the zygote are both of maternal origin. Recent studies have suggested that the maternal nucleolus, associated with other nucleoplasmic products, is essential for embryonic development [57]. Peripheral nucleoli were also reported by [58] where the nucleolar position in the nucleus was linked to the NORs location.…”
Section: Discussionmentioning
confidence: 88%
“…As expected, the detailed analysis of these embryos indicated defects in transcription. The embryo nucleolus is thus of maternal (oocyte) origin [9,10].…”
Section: Manipulating the Mammalian Oocyte Nucleolimentioning
confidence: 99%